Respuesta :
Answer:
To solve the equation S−6=13 S−6=13, you need to isolate S, S on one side of the equation. Here's how you do it:Add 6 to both sides of the equation:
S−6+6=13+6S−6+6=13+6
Simplify both sides:
S=19
S=19
So, S=19
Step-by-step explanation:
Answer:
S = 19
Step-by-step explanation:
for us to find the value of S, we need to isolate it on one side of the equation. so let's undo what's being done to S. Currently, 6 is being subtracted from S.
To undo this subtraction, we'll add 6 to both sides of the equation:
S - 6 + 6 = 13 + 6
On the left side, the -6 and +6 cancel out, leaving us with just S:
S = 13 + 6
So that means S = 19